Akhbār wulāt Khurāsān - al-Sallāmi, ʿAbd al-Ḥusayn b. Aḥmad, (Miras Maktoob, ISBN: 9789004365452., 2019)
The present work is not an historical text in the regular sense of the word. It is rather an inventory of as many citations and borrowings in later sources as possible from a text now lost. Written in Arabic, the Akhbār wulāt Khurāsān was started by ʿAbd al-Ḥusayn b. Aḥmad al-Sallāmi (d. 300/912) of Khwār near Bayhaq, whose account ran to the year 289/902, and then continued by his brother Abū ʿAlī b. Aḥmad al-Sallāmī, finishing in the year 344/955. As stated by the author of the present compilation, the work is important in that it is an early history of the governors of Khurāsān which was not written from religious or political motives. A trusted source, it saw at least three abridgements and is cited or used by many later authors, among them Abū Rayḥān Bīrūnī (d. 440/1048), ʿIzz al-Dīn b. al-Athīr (d. 630/1233), and ʿAbd al-Ḥayy b. Ḍaḥḥāk Gardīzī (fl. middle 5th/11th century)